2022
DOI: 10.5435/jaaos-d-21-00775
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Neural Networks Can Predict Early Failure of Cementless Total Hip Arthroplasty in Patients With Osteoporosis

Abstract: Background: Total hip arthroplasty (THA) done in the aging population is associated with osteoporosis-related complications. The altered bone density in osteoporotic patients is a risk factor for revision surgery. This study aimed to develop and validate machine learning (ML) models to predict revision surgery in patients with osteoporosis after primary noncemented THA. Methods: We retrospectively reviewed a consecutive series of 350 patients with osteoporosis (T-score less than or equal to 22.5) who underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…MPNN has been used in medical and orthopaedic research [ [18] , [19] , [20] ]. It allows for approximate solutions for complex problems to better understand the correlation strength between multiple variables [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…MPNN has been used in medical and orthopaedic research [ [18] , [19] , [20] ]. It allows for approximate solutions for complex problems to better understand the correlation strength between multiple variables [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using an ANN model can enable more appropriate and accurate processing of inputs that are incomplete or inputs that introduce noise[ 43 , 44 ]. Moreover, the results of Klemt et al [ 45 ] demonstrated its good application in binary data. In our research, the ANN model showed performance second only to that of the tree model in terms of original data and had considerable accuracy after cross-verification.…”
Section: Discussionmentioning
confidence: 99%